Migraine life-time prevalence in mental disorders: concurrent comparisons with first-degree relatives and the general population - Baptista, Trino; Uzcátegui, Euderruh; Arapé, Yinet; Serrano, Ana; Mazzarella, Xiorella; Quiroz, Segundo; Ramírez, Clara Isabel (Investigación Clínica, 2012)
The authors quantified the prevalence of migraine in subjects with mental disorders, first-degree relatives and the adult general population (GP) in Mérida, Venezuela. After validation, a modified, short version of the Lipton”™s diagnostic scale was administered to consecutively admitted in- and out-patients (n = 1059), their first-degree relatives (n = 445) and a probabilistic sample of the GP (n = 516). In the GP, the frequency of migraine (percentage and 95% confidence interval) was 14.9 (11.8-17.9). The migraine frequencies were (percentage and odd ratio probability against the GP: bipolar disorder (15.7%, p = 0.5), schizophrenia (8.3%, p = 0.08), depression and dysthimia (24.4%, p = 0.2), anxiety disorders (10.0%, p = 0.02), personality disorders (11.4%, p = 0.15), all other disorders (15.5%, p = 0.4), relatives of bipolar patients (4.4%, p < 0.001), relatives of schizophrenia patients (3.5%, p = 0.003), and relatives of patients with all other mental disorders (12.8%, p = 0.4). Migraine was more common in women (p < 0.001), and the bipolar patients presented the highest female to male ratio (8:1). A high variability was observed in migraine prevalence among the diagnostic categories, but it was particularly high in subjects with affective disorders, mainly in women, who thus deserve special attention from clinicians.